Bibliometric Exploration of Human Resource Innovation in the Tourism Industry - ER Ummi Kalsum; Ignatius Septo Pramesworo; Sri Budi Cantika Yuli; Kristina Sedyastuti; Adi Mursalin (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study explores innovation in Human Resource Management (HRM) in the tourism industry through bibliometric analysis. Using 70 relevant articles published between 2020 and 2024 from the Scopus database, this study uses bibliometric techniques such as simple count statistics, citation analysis, co-citation, bibliographic coupling, and network analysis. Findings reveal that human resource innovation plays a vital role in enhancing service quality, employee productivity, and organizational effectiveness in tourism. Key innovations include the use of artificial intelligence, video interviews, virtual and augmented reality in recruitment and training, and digital performance management systems. These tools significantly improve human resource efficiency and responsiveness. Moreover, green human resource practices and innovative employee welfare programs contribute to environmental performance and staff well-being. The study also emphasizes the need for continuous theoretical development to support sustainable human resource innovation. Future research should explore the integration of decision support systems, business analytics, and automation into human resource management, as well as their impact on employee satisfaction and organizational outcomes. Additionally, studies on green human resource management and inclusive policies can provide further insights into fostering a productive and sustainable work environment in tourism. This research provides a foundational understanding of current trends and offers guidance for further advancement in human resource innovation within the tourism industry.